PERANAN KADAR HEMATOKRIT, JUMLAH TROMBOSIT DAN SEROLOGI IgG - IgM ANTIDHF DALAM MEMPREDIKSI TERJADINYA SYOK PADA PASIEN DEMAM BERDARAH DENGUE (DBD) DI RUMAH SAKIT ISLAM SITI HAJAR MATARAM - Taufik S, Ahmad; Yudhanto, Didit; Wajdi, Farid; -, Rohad (journal of internal medicine, 2012)
The mortality rate of Dengue Haemorrhagic Fever is still high. It is still very difficult to predict shock. The commonlaboratory feature to predict shock are low platelet count, high hematocrit level and the positive result of serologic test (IgG andIgM antiDHF), but the validity remains controversial. This researh was determine many factor to predict shock in denguehemoragik fever patient . This research was case-control study. Data was collected from secondary data based on hematologic andserologic findings of patients with DHF who were hospitalized in Siti Hajar Islamic Hospital Mataram in the period of June 1,2005 until June 1, 2006. The samples of this study were patients that diagnosed as DHF based on WHO criteria and performedwith rapid serologic test Pan Blow? made in America, for Ig G and Ig M anti DHF. DHF patients that suffering shock werecatogorized as case group (n=47), and DHF patients without shock were control group (n=94). The total number of control groupwas two times of case group. Risk factor of shock were analyzed using chi-square test and multiple logistic regressions with levelof significance of < 0.05. The number of samples used in this study were 141 patients diagnosed as DHF, there were 47 patienstsDHF with shok and 94 DHF patients without shock. There was 70% patient with thrombositopenia and 44% patient had high rateof hematokrit more than 41.5 %. Shock was more frequent among pasients age more than 25 years, male, hematokrit level lessthan 40% and platelet count 50,000-100,000/ml. Based on univariate analysis, age, gender, high hematocrit value andtrombositopenia were not significantly different to predict shock. On multiple logistic regression methode, primery infection(IgM+ and IgG-) and secondary infection (IgG positif and IgM+/-) were not significantly different to predict shock. The conclusionof this study is high hematocrit value, platelet count and serology IgM or and IgG antiDHF there were no factor that couldpredict shock in DHF patients.